URGENSI PEMAHAMAN KONSEP DASAR IPS BAGI MAHASISWA PGSD - Kumala Sari, Cut (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is based on the importance of understanding social studies concepts for PGSD students as prospective teachers in elementary schools. Understanding social studies concepts is important for elementary school teachers to master as a provision for teaching their students. The aim of this research is to describe the urgency of understanding the basic concepts of social studies for PGSD students at Samudra Langsa University. The method used in this research is descriptive qualitative method. The data collection techniques used are questionnaires and documentation. The data analysis technique used in this research is content analysis based on literature study analysis. The results show that some students think it is important to have an understanding of the basic concepts of social studies as prospective elementary school teachers as indicated by the agree and disagree responses in the questionnaire. This research contributes to the view of the urgency of understanding the basic concepts of social studies for PGSD students as prospective teachers in elementary schools. Based on the results of this research, learning of social studies courses in the PGSD study program can be improved to support increased understanding of students' concepts. Keywords: Understanding of concepts, IPS